Recent bird observations from Kisar Island, Lesser Sundas - Trainor, Colin R (KUKILA, 2003)
ln September 2001 avifaunistic data were collected during a brief visit to the largely deforested island ofKisar (eastern Lesser Sundas). A total of 19 bird species were recorded including two new island records: Australian Pelican Pelecanus conspici1latus and Barn Swallow Himnclo rustica. Other interesting observations included the first sightings of the Little Friar bird Philemon citreogularis race hisserensis in almost lOO years. Study is needed to clarify the taxonomic distinctiveness of this taxon. The Rainbow Lorikeet Trichoglossus haematoclus and Olive-headed Lorikeet T. euteles, known from nineteenth century records, were not recorded and may now be extinct. The 'South-west' islands were little studied in the twentieth century. Ornithological surveys of still forested islands such as We tar, Romang and Babar are a priority.